Ifo World Economic Survey September 2002 - Gernot Nerb; Anna Stangl (Ifo World Economic Survey, 2002)
World Economic Climate worsened in July - Economic expectations became less optimistic - Inflation in 2002 expected to slow down - Short- and long-term interest rates expected to rise less than according to spring survey - Euro expected to strenghten further - Business needs to convey a positive image at Johannesburg summit
Keywords: 330